Strength Performance of Different Lightweight Concrete - Ikumapayi, Catherine; Habeeb, Olayemi; Ajayi, Joseph (Journal of Science, Technology and Innovation Research, 2026)
This study investigates the strength performance of different lightweight concretes using polystyrene, palm kernel shell, and pumice as replacements for traditional coarse aggregates in a consistent 1:2:4 mix ratio. Lightweight concrete offers potential advantages in reducing structural weight while maintaining adequate strength for various applications. A control mix of regular concrete with the same 1:2:4 ratio was prepared to serve as a benchmark. The mechanical properties of both the lightweight and control concretes were evaluated through compressive, tensile, and flexural strength tests at curing periods of 7, 14, 21, and 28 days. In addition, workability was assessed using slump tests, while water absorption tests were performed to evaluate porosity. The findings demonstrated that the lightweight aggregates considerably decreased the density of the concrete to values within the lightweight concrete range (1402–1979 kg/m³), as opposed to normal concrete density of not less than 2400 kg/m³. Pumice was the most effective lightweight aggregate overall, with a compressive strength of 11.22 MPa at 28 days (about 70% of the control) and improved flexural and tensile strength in comparison to other lightweight mixes. Although polystyrene demonstrated the lowest structural performance (2.05 MPa at 28 days), it gave exceptional moisture resistance and intermediate strength (6.30 MPa at 28 days) compared to palm kernel shell. The high porosity of pumice (15%), the low absorption of polystyrene (0.3%), and the intermediate value of palm kernel shell (8%), was all highlighted by water absorption tests. According to the results, polystyrene is a good lightweight aggregate for non-structural or insulating applications, palm kernel shell is recommended for moderate-strength, sustainable applications, and pumice is recommended for applications where strength and weight reduction must be balanced. Granite is still the best material for strong structural components.